Islam: the Natural Way - Hamid, Abdul Wahid (Delhi MELS, 1989)
Islam the Natural Way by Abdul Wahid Hamid presents Islam as a faith that aligns naturally with human reason, morality, and the innate sense of right and wrong. The book explains core Islamic beliefs, practices, and ethical teachings in a simple and accessible manner, emphasizing how Islam provides practical guidance for personal, social, and spiritual life. It serves as an introduction to the religion for both Muslims and non-Muslims.
Keywords: Islam $1 (BDoctrines | Islamic way of life | Comparative religion | Islamic beliefs and practicess